2012
DOI: 10.1038/nbt.2261
|View full text |Cite
|
Sign up to set email alerts
|

Should preclinical studies be registered?

Abstract: In recent years, numerous journals, regulators and ethics guidelines have adopted policies for prospective registration of clinical trials and full reporting of results. Whereas at one time, investigators published controlled clinical trials at their discretion, policies now compel prospective registration and deposition of trial results-including those that are negative and inconclusive-in publicly accessible databases 1 . In May, an editorial in Nature Biotechnology also supported the full disclosure of tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 11 publications
(10 reference statements)
0
63
0
Order By: Relevance
“…Irreproducible studies are a major source of waste in research [31], and the need to improve transparency and reporting in preclinical studies cannot be overemphasized. In fact, the registration of confirmatory preclinical research has previously been put forward as one method of addressing this problem [37][38][39]. Thus, whether trials of interventions intended to improve health, which are published in top behavioral health journals, are construed as clinical or preclinical trials, it is imperative that they be registered.…”
Section: Discussionmentioning
confidence: 99%
“…Irreproducible studies are a major source of waste in research [31], and the need to improve transparency and reporting in preclinical studies cannot be overemphasized. In fact, the registration of confirmatory preclinical research has previously been put forward as one method of addressing this problem [37][38][39]. Thus, whether trials of interventions intended to improve health, which are published in top behavioral health journals, are construed as clinical or preclinical trials, it is imperative that they be registered.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Several studies have shown that even the most promising findings from animal research often fail in human trials and are rarely adopted into clinical practice. [20][21][22] For example, one study found that fewer than 10% of highly promising basic science discoveries enter routine clinical use within 20 years.…”
Section: Lack Of Benefit For Humansmentioning
confidence: 99%
“…13 In addition to intensifying the systematic review effort, providing training in experimental design and adhering to higher standards of research conduct and reporting, prospective registration of preclinical studies, 54 and the public deposition of (both positive and negative) findings would be steps in the right direction. 18 Greater public accountability might be provided by including lay people in some of the processes of preclinical research such as ethical review bodies 55 and setting research priorities. 28 However, if animal researchers continue to fail to conduct rigorous studies and synthesise and report them accurately, and if research conducted on animals continues to be unable to reasonably predict what can be expected in humans, the public's continuing endorsement and funding of preclinical animal research seems misplaced.…”
Section: Time For Changementioning
confidence: 99%
“…Use meta-analysis of preclinical studies 134 Establish international multicenter phase III preclinical trials 135 Establish registries of preclinical studies 122,136 by guest on May 11, 2018 http://stroke.ahajournals.org/ Downloaded from…”
Section: Table 2 Improving the Predictiveness Of Preclinical Stroke mentioning
confidence: 99%